A study of health literacy and social media use of the students on vaccine preferences during COVID-19 pandemic in Turkey - Güzel Nur Yildiz; Abdulsamed Kaya; Bahar Çiftçi; Özgür Yildiz; Hanifi Körkoca (Wolters Kluwer Medknow Publications, 2023)
Background: It is unknown if health-care literacy and social media use of the students affect vaccine preferences during the COVID-19 pandemic. Objectives: The aim of the present research was to detect whether health-care literacy and social media use of the students affect vaccine preferences during the COVID-19 pandemic. Materials and Methods: The universe of the sample consisted of the students of a university in Mus Alparslan University. The sample of the research included students whose last digit of the school number is an odd number. Four hundred and twenty students participated into the study. The data of the study were collected through the "Sociodemographic Characteristics Questionnaire," "Health Literacy Scale (HLS)," and "Social Media Usage Scale (SMUS)." Results: The total score average of the students on the "HLS" was 42.74 ± 13.85 and the "SMUS" was 21.30 ± 7.38. It was determined that those who have preferred the "Sinovac" vaccine had higher score averages on the "Information Understanding Subdimension" and "HLS" than those who have preferred the Türkovac vaccine. Furthermore, it was determined that the score average of "Continuity Subdimension," "Competency Subdimension" and "Social Media Use Scale" were higher, and these differences were statistically significant. Conclusion: It was detected that the health literacy (HL) levels of the students were lower and they do not use social media competently. On the other hand, it was determined that social media use and HL affect the vaccine preferences.